Characterization of epitaxial CVD graphene on Ir(111)/α-Al2O3(0001) by photoelectron momentum microscopy. (1st June 2022) - Hashimoto, Eri; Tamura, Keigo; Yamaguchi, Hayato; Watanabe, Takeshi; Matsui, Fumihiko; Koh, Shinji
Abstract: We characterized CVD-grown graphene with high single-crystallinity on Ir(111)/ α -Al2 O3 (0001) by photoelectron momentum microscopy. A multi-functional photoelectron momentum microscope (PMM), which is installed with element-specific valence band photoelectron spectroscopy and X-ray absorption spectroscopy, is a complementary characterization tool to conventional methods, such as Raman spectroscopy and atomic force microscopy, for comprehensive and quantitative characterization of graphene/Ir(111). Using PMM, we characterized the properties of CVD-grown graphene including the single-crystallinity, number of layers, crystal orientation, and degree of interaction between graphene and Ir(111) and clarified the relationship between these properties and the CVD growth conditions.